Affinity‐switchable biotin probes for the analysis of enzymes and small reactive molecules on microarray platform. Issue 2 (7th August 2020) - Wu, Chia‐Lin; Fan, Chen‐Yo; Lin, Chun‐Cheng; Tan, Kui‐Thong
Abstract: Array‐based analytical platforms have a distinct advantage of being able to detect analytes rapidly and simultaneously with the use of very small quantities of reagents and samples. However, the analyses of enzyme activities using this technique remain challenging, as the heterogeneous interface between the enzyme in the solution and the probe on the array surface impede the efficient binding and the subsequent enzymatic reaction. In this paper, we showed that the combination of affinity‐switchable biotin (ASB) probes and a novel click‐chemistry based immobilization method can overcome this heterogeneity problem. Three ASB probes were synthesized for the detection of alkaline phosphatase, nitroreductase, and the fluoride ion. This approach can be applied to determine the relative levels of phosphatase in different cell lines. We believe that the new strategy holds great potential for the effective sensing of a wide range of biomolecules in the future. Abstract : In this paper, we introduce a general approach based on affinity‐switchable biotin probes to overcome the limitations of enzymatic activity analysis on microarray chips